Sociocultural implicit meaning in english translations of the Mu'allaqat - Al-Zidi, Kamal Chfat Shatti (2016)
Translation of literary texts, especially poetry, is one of the most difficult texts, which translators usually face since it requires mastery of the language system and the culture of the source language (SL) and target language (TL). Lacking the deep knowledge of the language, its system, and the culture might lead to wrong translation. Therefore, this study investigates the loss of sociocultural implicit meanings in the English translations of ancient Arabic poems Mu'aflaqaf. This study aims to fulfil the following specific objectives, (1) To identify the ST meanings of the Mu'allaqat based on eight topics, (2) To examine the types of loss of the socio-cultural implicit meanings in English translations of the Mu'allaqat and the reasons for the loss, and (3) To determine whether the translators of the Mu'allaqat have succeeded or not (unsuccessful) in transferring the socio-cultural implicit meanings from the ST to the TT. The study employs the quality assessment model (QA model) and the data collection is based on the criterion sampling. The data comprise two poems of the ST of the Mu'allaqaf, namely, Labid's poem and Tarafa's poem and also four English translations of these poems. The Mu'allaqafwere chosen because they are considered Masterpieces of the ancient Arabic poems and they are loaded with cultural signs. Data analyses of the study are based on two underlying theories: Newmark's approach of translation that consists of his semantic and communicative translation and Baker's taxonomy (1992) to translation equivalences, at word level, above word level, grammatical level, textual level and pragmatic level. The analysis involves first, explaining the implicit meanings of ST examples by consulting the Arabic references that interpret the Mu'allaqaf in terms of linguistic, semantic and rhetorical perspective. Second, comparing the ST implicit meaning with the translated versions of the Mu'allaqaf based on the identify theories to determine to what extent the meaning of the ST and the meaning of translated IT are similar or different. The translations of the Mu'allaqafwill be assessed by conducting translation quality assessment (TQA) to assess the level of success or failure in the examined translations. The findings of the study showed that there are two types of loss made by translators in translating the Mu'allaqaf such as: inevitable loss and avertable loss. The findings also revealed that the loss of socia-cultural implicit meaning occurred because of the inadequate use of the various types of equivalence and several strategies by the translators and absence of employing pragmatic and communicative equivalence.